The influence of stretch wrap containment force on load bridging in unit loads. Issue 11 (1st August 2018) - Park, Jonghun; Horvath, Laszlo; White, Marshall; Araman, Philip; Bush, Robert J.
Abstract : The term "load bridging" describes a phenomenon in which the physical interaction between various packaging components acts as a series of discrete loads in a given unit load and adds stiffness to the shipping pallet/load combination. Current pallet design practices often ignore the aspect of load bridging and assume that the pallet payload is flexible and uniformly distributed over the pallet surface. This can influence the load‐carrying capacity of the pallet. The study reported in this paper investigated the relationship between the stretch wrap containment force and load bridging in unit loads and the resulting unit‐load deflection. The experimental results of this study indicate that an increase in the stretch wrap containment force can improve the unit‐load deflection by as much as 81%. The influence of the stretch wrap containment force on pallet deflection is greatest for small packages and pallets with low stiffness. These experimental results provide useful information for realizing more efficient and sustainable unit‐load designs. Abstract : Current pallet design practices often ignore the aspect of load bridging and assume that the pallet payload is flexible and uniformly distributed over the pallet surface. The experimental results of this study indicate that an increase in the stretch wrap containment force can decrease the unit‐load deflection by as much as 81%. The influence of the stretch wrap containment force on pallet deflection is the greatest for small packages and low stiffness pallets.